Convergence between helminths and breast cancer: intratumoral injection of the excretory/secretory antigens of the human parasite Toxocara canis (EST) increase lung macro and micro metastasis - Aragón-Franco, Raúl; Ruiz-Manzano, Rocío Alejandra; Nava-Castro, Karen Elizabeth; Del Rìo Araiza, Víctor Hugo; Garay-Canales, Claudia Angelica; Pérez-Torres, Armando; Chacón-Salinas, Romel; Girón-Pérez, Manuel Iván; Morales-Montor, Jorge (Frontiers in Immunology, 2024)
Worldwide, breast cancer is the most important cancer in incidence and prevalence in women. Different risk factors interact to increase the probability of developing it. Biological agents such as helminth parasites, particularly their excretory/secretory antigens, may play a significant role in tumor development. Helminths and their antigens have been recognized as inducers or promoters of cancer due to their ability to regulate the host's immune response. Previously in our laboratory, we demonstrated that chronic infection by Toxocara cannis increases the size of mammary tumors, affecting the systemic response to the parasite. However, the parasite does not invade the tumor, and we decided to study if the excretion/secretion of antigens from Toxocara cannis (EST) can affect the progression of mammary tumors or the pathophysiology of cancer which is metastasis. Thus, this study aimed to determine whether excretion/secretion T. cannis antigens, injected directly into the tumor, affect tumor growth and metastasis. We evaluated these parameters through the monitoring of the intratumoral immune response. Mice injected intratumorally with EST did not show changes in the size and weight of the tumors; although the tumors showed an increased microvasculature, they did develop increased micro and macro-metastasis in the lung. The analysis of the immune tumor microenvironment revealed that EST antigens did not modulate the proportion of immune cells in the tumor, spleen, or peripheral lymph nodes. Macroscopic and microscopic analyses of the lungs showed increased metastasis in the EST-treated animals compared to controls, accompanied by an increase in VEGF systemic levels. Thus, these findings showed that intra-tumoral injection of T. canis EST antigens promote lung metastasis through modulation of the tumor immune microenvironment.